Standard handbook for electrical engineers - Fink, Donald G.; Beaty, Wayne H. (McGraw-Hill, 2000)
It's hard to think of the science and technology of electrical engineering without considering the one reference that has, for over 90 years, covered it like no other: the STANDARD HANDBOOK FOR ELECTRICAL ENGINEERS. Every technical breakthrough, every industry standard, every trend and defining issue--all have been a part of what has made the HANDBOOK a watershed reference for generations of engineers and technicians. One look at this new edition, featuring the insights of over60 expert contributors, and you'll see that this authoritative tradition is alive and well. Now more than ever, this standard-setting reference continues to give you the definitive, 360 degree look at the world of electricity, covering its generation, transmission, distribution, measurement, and use--including all the technical aspects needed by engineers working with electrical systems.